2022
DOI: 10.1039/d2tb00031h
|View full text |Cite
|
Sign up to set email alerts
|

Cubosomes as an emerging platform for drug delivery: a review of the state of the art

Abstract: Lipid-based drug delivery nanoparticles, including non-lamellar type, mesophasic nanostructured materials of lyotropic liquid crystals (LLCs), have been a topic of interest for researchers for their applications in encapsulation of drugs...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 230 publications
0
28
0
Order By: Relevance
“…Over the last decade, significant effort has been focused on designing and developing extremely efficient delivery systems that release active substances selectively and in a regulated manner. [146][147][148][149] Nonetheless, due to the inadequate solubility of drugs, 150,151 weak drug adsorptive capability, and complex drugrelease settings (e.g., gastric and intestinal environments), 152 attaining the long-term release of the drugs remains difficult. 153,154 Accordingly, BC-based scaffolds have potential drug delivery applications that can overcome many of the limitations of traditional drug delivery systems.…”
Section: Recent Advances On Bacterial Cellulose For the Delivery Of A...mentioning
confidence: 99%
“…Over the last decade, significant effort has been focused on designing and developing extremely efficient delivery systems that release active substances selectively and in a regulated manner. [146][147][148][149] Nonetheless, due to the inadequate solubility of drugs, 150,151 weak drug adsorptive capability, and complex drugrelease settings (e.g., gastric and intestinal environments), 152 attaining the long-term release of the drugs remains difficult. 153,154 Accordingly, BC-based scaffolds have potential drug delivery applications that can overcome many of the limitations of traditional drug delivery systems.…”
Section: Recent Advances On Bacterial Cellulose For the Delivery Of A...mentioning
confidence: 99%
“…Moreover, several studies reported a half maximal inhibitory concentration (IC50) value of monoolein-based cubosomes in the range of 30-100 µg/mL [56,[59][60][61]. Cubosomes are licensed and marketed as a non-parenteral medication in the United Kingdom and are on the US FDA's list of inactive ingredient guidelines [20,62].…”
Section: Principal Constituentsmentioning
confidence: 99%
“…; to the polymeric chain. However, drug delivery using hydrogels has not been free of obstacles, but continuous advancements are helping to settle on a hydrogel design competently conformed to specific drug delivery [ 10 , 11 ]. Due to several limitations of using natural hydrophilic polymers in hydrogel preparation, e.g., low thermal stability [ 12 ], absorption capacity [ 13 ], gel strength [ 3 ], etc.…”
Section: Introductionmentioning
confidence: 99%